2007
DOI: 10.1002/cne.21582
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics of photoreceptor synapse formation in the developing chick retina

Abstract: The cellular and molecular mechanisms underlying photoreceptor synaptogenesis are poorly understood. Furthermore, a detailed picture of the molecular composition of photoreceptor synapses, or their subtypes, is not yet available, nor do we know what differences, if any, exist among those subtypes. To address these questions, we investigated temporal and spatial patterns of expression and assembly of photoreceptor presynaptic components during chick embryo retinal development and early posthatched life by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 72 publications
1
42
0
Order By: Relevance
“…7). When that pattern was compared with the distribution of PSD95 and SV2, molecules previously shown to be components of photoreceptor synaptic terminals (Chen et al, 2005;Wahlin et al, 2007), clear colocalization was observed (Fig. 7).…”
Section: Subcellular Localization Of Immunoreactivity For Mbnl1 and 2mentioning
confidence: 71%
See 3 more Smart Citations
“…7). When that pattern was compared with the distribution of PSD95 and SV2, molecules previously shown to be components of photoreceptor synaptic terminals (Chen et al, 2005;Wahlin et al, 2007), clear colocalization was observed (Fig. 7).…”
Section: Subcellular Localization Of Immunoreactivity For Mbnl1 and 2mentioning
confidence: 71%
“…The isolated photoreceptors were readily identified in the dissociates as rods, double cones, and single cones based on their structure and the shape of their outer segments; single cone subtypes were distinguished based on their characteristic oil droplets (López et al, 2005). These identification criteria have been verified by PCR of individual cells (Wahlin et al, 2004;Huang and Adler, 2005;Wahlin et al, 2007). The segregation of MBNL1 and MBNL2 immunoreactivities was retained in the dissociated cells because, as shown in Figure 8, MBNL1 immunoreactivity was restricted to the synaptic terminal and MBNL2 to inner segments in all photoreceptor subtypes.…”
Section: Subcellular Localization Of Immunoreactivity For Mbnl1 and 2mentioning
confidence: 99%
See 2 more Smart Citations
“…The SV2 monoclonal antibody was raised against unique components of cholinergic synaptic vesicles from the electric organ of Discopyge ommata and recognizes a band of 75–110 kDa in immunoblots of brain synaptosomes (Wahlin et al, 2008). The antibody has been used as a marker of presynaptic terminals (D’Sa et al, 2007).…”
Section: Methodsmentioning
confidence: 99%